2011
DOI: 10.1002/pen.22020
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methylene blue dyes from wastewater using cellulose‐based superadsorbent hydrogels

Abstract: Superadsorbent cellulose‐graft‐acrylic acid (C‐g‐AA) hydrogels were successfully prepared via free radical polymerization in phosphoric acid solution. Phosphoric acid solution provides a homogeneous reaction system. The C‐g‐AA hydrogels have a porous network inner structure with cellulose as the backbone. The introduced carboxyl groups enable the C‐g‐AA hydrogels with good swelling property (swelling ratio 7327%) and excellent MB adsorption capacity (equilibrium adsorption amount 2197 mg g−1). The dynamic swel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…As it is shown above, the photochemically produced PEO hydrogels are less crosslinked than chemically crosslinked PVA, which reflects in a more expanded structure for PEO. Otherwise, at lower pH values, the hydroxyl groups are protonated and, therefore, reducing MB molecules adsorption binding sites …”
Section: Resultsmentioning
confidence: 99%
“…As it is shown above, the photochemically produced PEO hydrogels are less crosslinked than chemically crosslinked PVA, which reflects in a more expanded structure for PEO. Otherwise, at lower pH values, the hydroxyl groups are protonated and, therefore, reducing MB molecules adsorption binding sites …”
Section: Resultsmentioning
confidence: 99%
“…Various treatment processes such as ozonation , coagulation , ultrafiltration , oxidation , photocatalytic degradation , and adsorption are applied for dye removal from wastewater, but adsorption is considered as the most efficient method for the removal of dyes from wastewater . In the recent years, extensive research has been undertaken to develop alternative and cost‐effective adsorbents .…”
Section: Introductionmentioning
confidence: 99%
“…to color various products . It is reported that 2% of total dyes produced in its manufacturing units and 10–20% of dyes used for coloring different products are discharged in effluent water . However, most of the dyes are toxic and carcinogenic.…”
Section: Introductionmentioning
confidence: 99%
“…may effectively remove low concentration of dyes from water . In recent years, various polymeric hydrogels based on acrylic polymer/copolymers , semi‐ and full‐interpenetrating network (IPN) and natural polymers like chitosan , modified cellulose , alginates were tried for removal of dye from water. Natural polymers are abundant, renewable and biodegradable.…”
Section: Introductionmentioning
confidence: 99%